Dendritic Epidermal T Cells in Allergic Contact Dermatitis - Mraz, Veronika; Geisler, Carsten; Bonefeld, Charlotte Menné (Frontiers in Immunology, 2020)
Allergic contact dermatitis (ACD) is a common inflammatory skin disease with a prevalence of approx-imately 20% in the European population. ACD is caused by contact allergens that are reactive chemi-cals able to modify non-immunogenic self-proteins to become immunogenic proteins. The most fre-quent contact allergens are metals, fragrances, and preservatives. ACD clinically manifests as pruritic eczematous lesions, erythema, local papules, and oedema. ACD is a T cell-mediated disease, involv-ing both CD4+ and CD8+ T cells. In addition, gammadelta T cells appear to play an important role in the immune response to contact allergens. However, it is debated whether gammadelta T cells act in a pro- or anti-inflammatory manner. A special subset of gammadelta T cells, named dendritic epidermal T cells (DETC), is found in the epidermis of mice and it plays an important role in immunosurveillance of the skin. DETC are essential in sensing the contact allergen-induced stressed environment. Thus, allergen-induced activation of DETC is partly mediated by numerous allergen-induced stress proteins ex-pressed on the keratinocytes (KC). Several stress proteins, like mouse UL-16-binding protein-like tran-script 1 (Mult-1), histocompatibility 60 (H60) and retinoic acid early inducible-1 (Rae-1) α-ε family in mice and major histocompatibility complex (MHC) class I – chain-related A (MICA) in humans, are upregulated on allergen-exposed KC. Allergen-induced stress proteins expressed on the KC are con-sequently recognized by NKG2D receptor on DETC. This review focuses on the role of gammadelta T cells in ACD, with DETC in the spotlight, and on the role of stress proteins in contact allergen-induced activa-tion of DETC.